Alterations of microRNAs and their predicted targeting mRNAs expression in RAW264.7 macrophages infected with Omp25 mutant Brucella melitensis. Issue 6 (August 2018) - Zhu, Huapei; Jiao, Hanwei; Nie, Xin; Li, Baobao; Xu, Kailian; Pang, Feng; Cao, Ruiyong; Zhu, Shu; Yang, Xiaojian; Zhang, Zhenxing; Peng, Dongmei; Li, Yaying; et al.
Brucellosis is a worldwide zoonosis caused by Brucella species and represents a serious threat to both human and animal health. Omp25 is an important immunogenic and protective antigen in Brucella species; however, the functional mechanism of Omp25 in macrophages has not yet been elucidated. Here, we constructed a Brucella melitensis omp25 deletion mutant (M5-90-Δ omp25 ) and performed microRNA (miRNA) profiling of infected RAW264.7 cells. Eight differentially expressed miRNAs ( mmu-miR-146a-5p, mmu-miR-155-5p, mmu-miR-3473a, mmu-miR-149-3p, mmu-miR-671-5p, mmu-miR-1224-5p, mmu-miR-1895, and mmu-miR-5126 ) were identified, with quantitative real-time PCR (qRT-PCR) analysis confirming the up-regulation of mmu-miR-146-a-5p and mmu-miR-155-5p and down-regulation of mmu-miR-149-3p and mmu-miR-5126 . mRNA profiling of B. melitensis M5-90-Δo mp25 -infected RAW264.7 cells identified 967 differentially expressed genes (DEGs) (fold change ≥ 2). Among these, we focused on genes that were predicted by TargetScan, miRanda, and PicTar to be the potential targets of the differentially expressed miRNAs. The results suggested that 17 separate genes are potentially targeted by mmu-miR-149-3p, with one of these genes, Tbr1, also targeted by mmu-miR-5126 . qRT-PCR analysis confirmed the up-regulation of nine of the predicted target genes. Our findings provide important information about the functional molecules in host cells, including miRNA and their target genes, affected by Omp25 from Brucella . This information is particularly valuable for the prophylaxis and treatment of brucellosis.